Obstacle course the everyday struggle to get an abortion in America - Cohen, David S., 1972-; Joffe, Carole E. (University of California Press, 2020)
"This book tells the real story of abortion in America, one that captures a disturbing reality of sometimes insurmountable barriers put in front of women trying to exercise their legal rights to medical services. Without the efforts of an unheralded army of doctors, nurses, social workers, activists, and volunteers, what is a legal right would be meaningless for the almost one million people per year who get abortions. There is a better way--treating abortion like any other form of health care--but the United States is a long way from that ideal"--